Fibroblastic reticular cells of the lymphoid tissues modulate T cell activation threshold during homeostasis via hyperactive cyclooxygenase-2/prostaglandin E2 axis - Miao Yu (Nature Portfolio, 2017)
Abstract Fibroblastic reticular cells (FRCs) in the T cell zone of lymph nodes (LNs) are pivotal for T cell survival, mobility, and peripheral tolerance. Here, we demonstrate that during homeostasis, FRCs also suppress T cell activation via producing high level of prostaglandin E2 (PGE2) due to their thousands-fold higher cyclooxygenase-2 (COX-2) expression than immune cells. This hyperactive COX-2/PGE2-induced suppression is evident during antigen-specific and non-antigen-specific activations. It is implicated as suppressed TCR-signaling cascades, reduced alterations in activation markers, and inhibited cytokine production of freshly isolated T cells or T cells co-cultured with FRCs compared with those cultured without FRCs. Different from T cell dysfunction, this FRC-mediated suppression is surmountable by enhancing the strength of stimulation and is reversible by COX-2 inhibitors. Furthermore, T cells in the FRC environment where Cox-2 is genetic inactivated are more sensitive and rapidly activated upon stimulations than those in WT environment. Significantly, FRCs of human lymphoid organs manifest similar COX-2/PGE2 hyperactivity and T cell suppression. Together, this study identifies a previously unappreciated intrinsic mechanism of FRCs shared between mice and humans for suppressing T cell sensitivity to activation via PGE2, underscoring the importance of FRCs in shaping the suppressive milieu of lymphoid organs during homeostasis.